ChemInform Abstract: Lanthanide(III)‐Bis(cyclopropylethinylamidinates): Synthesis, Structure, and Catalytic Activity. Issue 35 (September 2015) - Sroor, Farid M.; Hrib, Cristian G.; Hilfert, Liane; Jones, Peter G.; Edelmann, Frank T.
Abstract It is demonstrated, that a bis‐neodym complex BND efficiently catalyzes the addition of primary aromatic amines to carbodiimides producing N‐arylguanidines in high yields.